Arginine methylation in the E2F1 pathway - Zheng, S (2013)
The E2F1 pathway plays an important role in coordinating early cell cycle progression. Deregulation of the E2F1 pathway, which may be brought about by somatic mutations in genes such as INK4A, RB1 and CDK4, is found in a majority of cancers. The transcription factor E2F1 is able to activate genes involved in proliferation as well as apoptosis, but the mechanisms that govern these opposing biological effects remain poorly understood. In this study, I would describe how E2F1 activity can be regulated by two novel post-translational modifications which result in different functional consequences. It was found that PRMT1 asymmetrically methylates E2F1 at R109, while PRMT5 symmetrically methylates R111 and R113. The symmetric dimethyl marks on E2F1 promoted the recruitment of Skp2, a component of the E3 ubiquitin ligase complex, which coincided with decreased protein stability and transcriptional activity, as well as enhanced cell proliferation and reduced apoptosis. The asymmetric dimethyl marks on E2F1 was found to hinder symmetric dimethylation, leading to reduced cell proliferation and enhanced apoptosis. The competition between PRMT1 and PRMT5 at the E2F1 RG-rich motif was found to be regulated by the adjacent cyclin A binding site. Induction of DNA damage, which resulted in decreased cyclin A level, corresponded to an increase in PRMT1 and decrease in PRMT5 binding. This study uncovers a new mechanism in E2F1 regulation and establishes the importance of arginine methylation in cell proliferation and apoptosis.